2013
DOI: 10.1039/c3ta13030d
|View full text |Cite
|
Sign up to set email alerts
|

A novel magnetic recyclable photocatalyst based on a core–shell metal–organic framework Fe3O4@MIL-100(Fe) for the decolorization of methylene blue dye

Abstract: We describe a novel type of magnetic recyclable Fe 3 O 4 @MIL-100(Fe) photocatalyst on the basis of a porous metal-organic framework (MOF) and its photocatalytic activities in the photodegradation of methylene blue (MB) dye. It was found that Fe 3 O 4 @MIL-100(Fe) exhibited photocatalytic activity for MB dye degradation under both UV-vis and visible light irradiation, and the MB decolorization over the Fe 3 O 4 @MIL-100(Fe) photocatalyst followed first-order kinetics. Moreover, it can be easily separated and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
134
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(141 citation statements)
references
References 36 publications
(52 reference statements)
4
134
1
2
Order By: Relevance
“…Moreover, we also measured the chemical oxygen demand (COD) to verify the complete oxidation of MB (Figure 4c). The trends of the optical density and COD decreases were nearly identical, which suggested that the decoloration of MB was mainly due to the complete oxidation of MB into CO2 [20][21][22][23][24][25]. Generally, many Fenton systems generate oxidative radicals and other non-radical species [26].…”
Section: Decoloration Of Mb In the Ftcnc-h 2 O 2 Fenton-like Systemmentioning
confidence: 69%
“…Moreover, we also measured the chemical oxygen demand (COD) to verify the complete oxidation of MB (Figure 4c). The trends of the optical density and COD decreases were nearly identical, which suggested that the decoloration of MB was mainly due to the complete oxidation of MB into CO2 [20][21][22][23][24][25]. Generally, many Fenton systems generate oxidative radicals and other non-radical species [26].…”
Section: Decoloration Of Mb In the Ftcnc-h 2 O 2 Fenton-like Systemmentioning
confidence: 69%
“…Since the first report of photocatalytic activity in MOF-5, MOFs have been increasingly used as novel photocatalysts Nano Res. [13,14]. However, they still suffer from some drawbacks, such as a high recombination probability of photoexcited charge carriers.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, considering its photoactive property, MIL-100(Fe) is a promising candidate for the development of efficient photocatalysts [14,27]. Toward this end, we report on a set of noblemetal@MIL-100(Fe) (M = Au, Pd, Pt) nanocomposites (denoted M@MIL-100(Fe)) fabricated using a facile room-temperature photodeposition technique without the use of any chemical reducing agents or organic stabilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Using semiconductor QDs and MOFs as photo-catalysts have their own advantages and disadvantages [29]. By integrating such semiconductor QDs-MOF hybrid materials, they are expected to possess advanced properties originating from the two different components and also overcome their individual shortages [30][31][32]. To date, there has been progress on the studies of semiconductor-MOF heterostructures for photo-catalytic activity.…”
Section: Issn: 2320-5407mentioning
confidence: 99%